Interference between roe deer and Northern chamois in the Italian Alps: are Facebook groups effective data sources?. Issue 3 (4th May 2018) - Mori, Emiliano; Di Bari, Pietro; Coraglia, Marco
Abstract : The number of wildlife watchers and photographers sharing data on online platforms and social networks is increasing; images of interspecific relationships are among the most popular. Behavioural interference among wild ungulates is rare, but some occurrences of this behaviour may have been reported on wildlife-dedicated Facebook groups. We searched for information on the behaviour of roe deer, expanding towards high altitudes, in presence of Northern chamois. Our research was carried out on Facebook groups/pages of natural photography and wildlife watching. We analysed a total of 67 observations out of 73 collected: in over 67% of them, roe deer and chamois shared the same feeding site without interacting. In 28% of cases, female chamois chased and displaced female roe deer at feeding sites and only in the remaining 5% male roe deer displaced chamois (mainly at waterholes). Even if no data are available on distribution trends of these species, we suggest that these interactions may increase with increasing global warming and range expansion of roe deer – a hypothesis that deserves further attention and field studies.